World Order : Reflections on the Character of Nations and the Course of History - Kissinger, Henry (London Penguin Books, 2014)
Henry Kissinger offers in World Order a meditation on the roots of international harmony and global disorder. There has never been a true "world order," Kissinger observes. For most of history, civilizations defined their own concepts of order. Each considered itself the center of the world and envisioned its distinct principles as universally relevant. China conceived of a global cultural hierarchy with the Emperor at its pinnacle.
Include Notes and Index
Keywords: World Politics -- 21st Century -- Security, International -- International Relations -- Geopolitics